Nilai Pendidikan Islam dalam Doi' Balanca pada Pernikahan Adat Bugis - Shaleh, Muhammad; Muhaemin; Irwan; Imran Saputra; Uswatun Hasanah (TAUJIH: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the implementation of the Doi’ Balanca (uang panai) tradition in marriage practices and to examine the Islamic educational values embedded within this tradition among the Bugis community in Desa Harapan, Barru Regency. Employing a descriptive qualitative approach through field research, data were collected via in-depth interviews, participatory observation, and documentation of traditional wedding processes. Thematic analysis was conducted through data reduction and categorization. The findings reveal that the practice of Doi’ Balanca is not merely a symbolic customary requirement but also embodies moral, spiritual, and social values such as responsibility, hard work, respect for women, as well as familial deliberation and togetherness. Within the framework of Islamic education, these values reflect core principles such as mas’uliyyah (responsibility), shura (consultation), ukhuwah (brotherhood), ‘adl (justice), and zuhd (modesty), all of which align with the objectives of Islamic character education. However, the tradition faces challenges from materialistic tendencies and social prestige, which risk distorting its spiritual significance. The study’s implications highlight the strategic role of Islamic education in reinterpreting and guiding the practice of Doi’ Balanca to remain aligned with Sharia principles through educational, humanistic, and contextual approaches. This research is expected to contribute significantly to the development of character education curricula rooted in local culture and serve as a reference for religious leaders, educators, and communities in understanding tradition as a medium for education rather than a mere legacy.